Z- Source Inverter Based Dynamic Voltage Restorer for the Mitigation of Voltage Sag/Swell - K. Prameela; D. Vijay Kumar; B. Trinadha (International Journal of Applied Power Engineering (IJAPE), 2016)
This paper uses super capacitor as the energy storage device for the DVR to compensate voltage sag, voltage swell and harmonics due to addition of nonlinear load in the distribution line. Based on this topology, DVR consist of super capacitor, z source inverter and injection transformer. Super capacitor produces the necessary dc voltage which is given as the input voltage to the z-source inverter; provide the necessary injecting voltage, which has to be restored. A new topology based on Z-source inverter is presented in order to enhance the voltage restoration property of dynamic voltage restorer. Z-source inverter would ensure a constant DC voltage across the DC-link during the process of voltage compensation. The modeling of Z-source based dynamic voltage restorer is carried out component wise and their performances are analyzed using MATLAB software